(-3+x-x)(-2)=

Simple and best practice solution for (-3+x-x)(-2)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (-3+x-x)(-2)= equation:


Simplifying
(-3 + x + -1x)(-2) = 0

Combine like terms: x + -1x = 0
(-3 + 0)(-2) = 0
(-3)(-2) = 0

Multiply -3 * -2
6 = 0

Solving
6 = 0

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| 2(6-t)=15(2t) | | 4x+1*4x+1= | | 4/3*9/8/9/4 | | 0.5x-0.125=-0.33333333333333x+0.25 | | 6x-23=17-6(5-2x) | | (4x^3y^5)= | | 2x+y+z=3 | | 34x-10x=360x | | 2(x-2)+4=10x | | 0.5x-0.125=0.33333333333333x+0.25 | | x^2+4x+27=-8x-5 | | 3r(2)-21=-18r | | 8x+12-5x=21 | | k(2)-3k-18=0 | | 9-5x+1=15 | | 8/3x-2(x+3)=14/3x-10 | | 11x+8=(x+2)(3x+4) | | 32r^3+4s^3=0 | | 16-3(8-3)/5 | | 300x-0.54=100x+0.46 | | 8x/3x-1=2x/1 | | 2.2x-40=1.1x+4 | | 4x+3(12-2x)=2(x+2) | | 6x-14.5=x | | 10x^2/20x^2-25x | | 5p(2)-245=0 | | 0.3x+0.1=-0.8 | | -3x-43=2(x+2)+8 | | -5x-13=-28 | | 3w-2(4-8w)=8w+25 | | z^2-z+0.25=0 | | 9=-7-3-a+a |

Equations solver categories